Implementing Interventions Under “National Action Plan for Snakebite Envenoming (NAPSE) in India”: Challenges, Lessons Learnt and Way Forward for Stakeholders Participatory Approach - Ajit Dadaji Shewale; Dipti Mishra; Simmi Tiwari; Tushar Nanasaheb Nale; Jitesh Kuwatada; Nidhi Khandelwal (Tropical Medicine and Infectious Disease)
Snakebite envenoming remains a critical yet underrecognized public health issue, particularly in tropical and subtropical regions, with India bearing nearly half of the global burden of snakebite-related deaths. Despite its significant impact, underreporting, delayed medical intervention, and insufficiently trained healthcare professionals continue to exacerbate the problem. In response, the Government of India launched the National Action Plan for Prevention and Control of Snakebite Envenoming (NAPSE) in March 2024, aiming to halve snakebite-related deaths by 2030. Key challenges during the development and implementation of NAPSE included the limited multisectoral engagement initially, variations in state-level capacities, and logistical barriers in reaching remote populations. Lessons learned include the value of early stakeholder consultations, the importance of inter-ministerial collaboration, and the need for continuous community engagement. This comprehensive strategy emphasizes strengthening surveillance systems, enhancing anti-snake venom (ASV) distribution and quality, improving healthcare infrastructure, and promoting community awareness through a One Health approach. The plan also addresses critical challenges such as inadequate training at primary healthcare levels, inconsistent ASV supply, and inefficient emergency referral systems. By fostering multisectoral collaboration and targeted interventions, such as strengthening Regional Venom Centres and establishing Poison Information Centre, targeted training, and awareness campaigns, NAPSE aims to reduce mortality and disability associated with snakebite envenoming, aligning with global health objectives and setting an example for regional efforts in Southeast Asia.